A NOTE ABOUT THE NORM OF GRADIENT - Marcel, ABAS (Trends in education, 2011)
If the gradient of a function is non-zero in a point, it can be interpreted as the direction in which the function changes most quickly. In this contribution we show that there is a possibility to establish the direction even if the gradient is zero and that this can be done with knowledge which students have it their stage of study.
Keywords: gradient; norm of vector; the direction of the maximum rate of change.